Музеи как безбарьерное пространство для слепых - Якубовски, М. В.
The article presented the concept of creation of a barrier-free space for blind and as object is elected the museum. We represent some aspects of this concept examples a city administ ration of Warsaw –message boards at an entrance, variety of ways of submission of information. placement of information,marking of space. All actions directed on creation of barrier-free space for blind have to be carried out in close cooperation with group of visually impaired and blind consultants.
Keywords: Тифлографикa; Музеи